2020
DOI: 10.3168/jds.2020-18542
|View full text |Cite
|
Sign up to set email alerts
|

Feeding rumen-protected lysine prepartum increases energy-corrected milk and milk component yields in Holstein cows during early lactation

Abstract: kg/d, respectively). Plasma concentrations of Lys prepartum (69.8 ± 1.8 µM) increased for cows in PRE-L compared with those in PRE-C (62.5 ± 1.3 µM). In conclusion, RPL consumed prepartum tended to increase postpartum DMI and increased energy-corrected milk and milk component yields. This indicates that prepartum supply of intestinally available Lys is pertinent to postpartum performance. However, postpartum supply of intestinally available Lys had no effect on cows' performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 48 publications
11
38
1
1
Order By: Relevance
“…Thus, the unchanged N-NH 3 concentration in the rumen indicated that extra N intake from ATC supplementation contributed to microbial protein synthesis, rather than N-NH 3 production. Many studies have demonstrated that the supply of intestinally available limiting AA is pertinent to milk yield and milk protein yield by decreasing protein mobilization and increasing accretion [ 57 , 58 ]. According to the AA profile of ATC, TAA accounted for 17.27% of ATC (DM basis).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the unchanged N-NH 3 concentration in the rumen indicated that extra N intake from ATC supplementation contributed to microbial protein synthesis, rather than N-NH 3 production. Many studies have demonstrated that the supply of intestinally available limiting AA is pertinent to milk yield and milk protein yield by decreasing protein mobilization and increasing accretion [ 57 , 58 ]. According to the AA profile of ATC, TAA accounted for 17.27% of ATC (DM basis).…”
Section: Discussionmentioning
confidence: 99%
“…All experimental procedures were approved by the University of Illinois (Urbana-Champaign) Institutional Animal Care and Use Committee (#18157) and were a part of a larger study (Fehlberg et al, 2020). A detailed description of this study is provided in Fehlberg et al (2020). Briefly, the experimental period was from September 2018 to June 2019.…”
Section: Jdsmentioning
confidence: 99%
“…Due to variation in actual calving day, not all cows had urine collected for wk −3 or −4. The number of cows per treatment was calculated to detect a minimum of 7% difference in postpartum DMI between groups, assuming a power of 0.9 and a 2-tailed α of 0.05 (Fehlberg et al, 2020). Cows were manually stimulated until urination, and approximately 80 mL of voided urine was collected via free-catch into a 100-mL urine collection tube (Fisher Scientific) during mid-stream of urination.…”
Section: Jdsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have revealed that Lys is also an important bioactive molecule that plays key roles in signaling pathways and metabolic regulation, including energy, glucose, and lipid metabolism ( Hu and Guo, 2020 ; Kong et al., 2020 ; Wu, 2009 ). For example, a study indicated that dietary Lys restriction could enhance milk fat accumulation in dairy cows ( Křížová et al., 2010 ), and prepartum supply of intestinally available Lys in Holstein cows could improve milk fat and energy-corrected milk yields ( Fehlberg et al., 2020 ). However, we speculate that Lys metabolism and functions in dairy cows are inferred from pre-ruminants, and adult ruminants are distinguished from pre-ruminants by rumen microbial fermentation ( Malmuthuge and Guan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%